The Effect of Ketamine on Acute and Chronic Wound Pain in Patients Undergoing Breast Surgery: A Meta‐Analysis and Systematic Review. Issue 3 (13th November 2020) - Bi, Yaodan; Ye, Yu; Zhu, Yinchao; Ma, Jun; Zhang, Xiuqian; Liu, Bin
Abstract: Introduction: Perioperative use of ketamine has been discussed widely in many kinds of surgery. The aim of our study was to evaluate the short‐term and long‐term benefits and safety of ketamine after breast surgery. Method: We performed a quantitative systematic review. We included randomized controlled trials that compared intravenous administration of ketamine to a placebo control group, or compared bupivacaine in combination with ketamine to bupivacaine alone in thoracic paravertebral blocks or pectoral blocks among patients undergoing breast surgery. The primary outcome was postoperative pain intensity. Secondary outcomes included cumulative opioid consumption during the 0‐ to 24‐hour postoperative period, the effect on postmastectomy pain syndrome, the effect on postoperative depression, and the adverse events associated with the use of ketamine. Results: Thirteen randomized controlled trials with 1, 182 patients were included for analysis. Compared with placebo, intravenous ketamine was effective in reducing wound pain intensity during the first 6 hours after surgery (weighted mean difference [WMD] −0.83; 95% confidence interval [CI] −1.65, −0.01; P = 0.048) and during the first 24 hours after surgery (WMD −0.65; 95% CI −0.95, −0.35; P < 0.001), and in decreasing opioid consumption (WMD −4.14; 95% CI −8.00, −0.29; P = 0.035) during the first 24 hours after surgery, without increasing the risks for gastrointestinal and central nervous system adverse events. Adding ketamine to bupivacaine in thoracic paravertebral blocks was also effective in reducing postoperative wound pain during the first 6 hours after surgery (WMD −0.59; 95% CI, −1.06, −0.12; P = 0.014) and during the first 24 hours after surgery (WMD −0.90; 95% CI −1.27, −0.53; P < 0.001), and in decreasing opioid consumption (WMD − 4.59; 95% CI −5.76, −3.42; P < 0.001) during the first 24 hours after surgery. Perioperative use of ketamine was associated with improved postoperative depression symptoms (standardized mean difference −0.80; 95% CI − 1.34, −0.27; P = 0.003) and less incidence of postmastectomy pain syndrome (relative risk 0.79; 95% CI 0.63, 0.99; P = 0.043). Conclusion: Ketamine is an effective and safe multimodal analgesic in patients undergoing breast surgery, administered both intravenously and when added to bupivacaine in paravertebral blocks. In addition, ketamine showed a long‐term benefit for preventing postoperative depression and postmastectomy pain syndrome.